2013
DOI: 10.1097/mbc.0b013e328360c75a
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume is not associated with platelet reactivity and the extent of coronary artery disease in diabetic patients

Abstract: Platelets play a central role in the pathogenesis of coronary artery disease (CAD). Mean platelet volume (MPV) is an indicator of platelet activation, and has been demonstrated to be correlated with platelet reactivity. Diabetic patients have been shown to have larger MPV, that may contribute to higher platelet reactivity and atherothrombotic complications observed in these patients. Therefore, the aim of the current study was to investigate whether MPV is associated with platelet reactivity and the extent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 29 publications
2
32
1
2
Order By: Relevance
“…Left anterior descending artery (LAD) involvement is associated with high MPV level in patients with non-STEMI, and this may be another factor causing large infarct size in addition to the microvascular obstruction [16]. Although contradictory data exists, some studies showed a correlation of MPV with severity of coronary artery disease [17,18]. Sarikaya et al [5] showed MPV levels were higher in diabetic patients with myocardial perfusion defects than in those without.…”
Section: Discussionmentioning
confidence: 99%
“…Left anterior descending artery (LAD) involvement is associated with high MPV level in patients with non-STEMI, and this may be another factor causing large infarct size in addition to the microvascular obstruction [16]. Although contradictory data exists, some studies showed a correlation of MPV with severity of coronary artery disease [17,18]. Sarikaya et al [5] showed MPV levels were higher in diabetic patients with myocardial perfusion defects than in those without.…”
Section: Discussionmentioning
confidence: 99%
“…Bu tekniği kullanarak gerçekleştirilen üç ayrı araştırmada MPV ve diğer trombosit parametreleri ile trombosit agregasyonu arasında bir ilişkinin varlığı gösterilememiştir [9][10][11] . MPV esasen trombosit fonksiyonunun değil, trombosit üretiminin bir göstergesidir.…”
Section: Sayın Editörunclassified
“…Beyan et al [2] did not show any correlation between platelet indices measured including platelet count, MPV, platelet mass, platelet distribution width and plateletcrit and platelet aggregation responses with collagen, adenosine diphosphate and epinephrine obtained with light transmission turbidimetric platelet aggregometry in healthy subjects. Also, De Luca et al [3] carried out a cohort study including 1016 diabetic patients undergoing coronary angiography and found that MPV was not related to platelet reactivity. Actually, MPV related to the platelet production (thrombopoiesis) not platelet function or activation.…”
Section: To the Editormentioning
confidence: 99%